Variety of Prawn species - Mumbai Archive Project Team (Jio Institute, 2024)
Local fishermen catch a variety of prawn species off the coast of Mumbai. Whiteleg prawn (king prawn), black tiger shrimp, different species of Solenocera or pink shrimp (seen here), green tiger prawn, and greasyback shrimp are among them.